Harvard Business Review on Making Smarter Decisions - Authors (Harvard Business Press, 2007)
Decisions are the coin of the realm in business. Every success, every mishap, every opportunity seized or missed stems from a decision someone made - or failed to make. Brimming with potent suggestions from esteemed experts - including Jeffrey Pfeffer, Robert Sutton, Ram Charan, Thomas Davenport, and John Hammond - this handy volume offers a wealth of tools and practices to guide you through your most difficult choices.